Prediction of floor responses to crowd bouncing loads by response reduction factor and spectrum method. Issue 7 (May 2021) - Chen, Jun; Ren, Jingya; Racic, Vitomir
Bouncing is a typical rhythmic crowd activity in entertaining venues, such as concert halls and stadia. When the activity's frequency is close to the natural frequency of the occupied structure, the corresponding bouncing loads can cause intense structural vibrations resulting in vibration serviceability problems, even structural damage. This study suggests a method for prediction of vibration response due to crowd bouncing by a response reduction factor (RRF) in conjunction with a previously established response spectrum approach pertinent to a single person bouncing. The RRF is defined as a ratio between structural responses with and without taking into account synchronization of body movements of individuals in a bouncing crowd. The variations of RRF with number of persons, structural frequency, bouncing frequency and structural damping ratios have been studied using experimental records of crowd bouncing loads. Based on the findings a practical design curve for RRF has been proposed. Application of the proposed method has been validated on numerical simulations and field measurements of a long-span floor subjected to crowd bouncing loads.